Collaborative learning: report of an experience of continuing education with teachers who work in professional and technological education - Rossini, Alexandre Montagna; Vieira, Amanda Ribeiro; Caetano, Plínio Alexandre dos Santos; Moraes, Rozangela Nogueira de (Revista Hipótese, 2019)
The Federal Institute of São Paulo (IFSP), through Resolution 138, from December 8, 2015, approved its policy of Continuing Teacher Training and IFSP Campus Sertãozinho, through Ordinance SRT.0021 / 2015 from February 27, 2015, constituted its Team. Among the many activities developed by the IFSP Campus Continuing Teacher Training Team, this paper aims to describe a training activity on collaborative learning developed with the teachers of this camp. The activity, which was divided into stages, counted on the collaborative participation of those involved and the use of information technology and communication.